2012
DOI: 10.2174/138920112798868746
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals Resveratrol and Sulforaphane as Potential Agents for Enhancing the Anti-Tumor Activities of Conventional Cancer Therapies

Abstract: Even though conventional cancer therapies, comprising surgery and chemo- and radiotherapy, play an important role in the treatment of most solid tumours, successful therapeutic outcome is often limited due to high toxicity and related side-effects, as well as the development of multi-drug resistances. Therefore, there is need for new therapeutic strategies not only to obtain higher treatment efficacy, but also for the reduction of toxicity and adverse effects. Emerging evidence suggests that natural compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…This finding was substantiated by our observations that plasmid or lentiviral vector-mediated expression of 3'UTR-less c-MYC cDNA and chemotherapeutic drug cisplatin- or doxorubicin-induced endogenous c-MYC accumulation was also suppressed by either SFN or miR-214. SFN acts as a potent chemopreventive agent against cancer through modulating multiple signaling pathways involved in cell growth, apoptosis, inflammation and self-renewal of CSCs [4, 5, 38, 39]. Our study provides key mechanistic insights into how sulforaphane inhibits c-MYC activity, thereby exerting its anti-cancer and CSC effects.…”
Section: Discussionmentioning
confidence: 94%
“…This finding was substantiated by our observations that plasmid or lentiviral vector-mediated expression of 3'UTR-less c-MYC cDNA and chemotherapeutic drug cisplatin- or doxorubicin-induced endogenous c-MYC accumulation was also suppressed by either SFN or miR-214. SFN acts as a potent chemopreventive agent against cancer through modulating multiple signaling pathways involved in cell growth, apoptosis, inflammation and self-renewal of CSCs [4, 5, 38, 39]. Our study provides key mechanistic insights into how sulforaphane inhibits c-MYC activity, thereby exerting its anti-cancer and CSC effects.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have shown RES may sensitize cells by blocking chemotherapy-induced NFκB activity (44). However, in our cancer cell lines, RES did not inhibit NFκB activity (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…It has been extensively studied for its antioxidant, anti-aging and anti-inflammatory activities181920212223. In addition, in vivo and in vitro studies showed that RES possesses potential anti-tumor activity against several malignancies24252627. According to our previous study, RES potentiates the cytotoxic properties of DOX in MCF-7, HeLa and HepG2 cells via P-gp inhibition and downregulation of MDR1 gene28.…”
mentioning
confidence: 93%